Abstract
We investigate the maximum directed cut (MaxDC) problem by designing a spectral partitioning algorithm. Given a directed graph with nonnegative arc weights, we wish to obtain a bipartition of the vertices such that the total weight of the directed cut arcs is maximized. Relaxing the MaxDC problem as a quadratic program allows us to explore combinatorial properties of the optimal solution, leading to a 0.272-approximation algorithm via the technique of spectral partitioning rounding.
Similar content being viewed by others
Explore related subjects
Discover the latest articles and news from researchers in related subjects, suggested using machine learning.References
Beckenbach E, Bellman R (1961) An introduction to inequalities. Random House, New York
Feige U, Jozeph S (2015) Oblivious algorithms for the maximum directed cut problem. Algorithmica 71:409–428
Goemans MX, Williamson DP (1995) Improved approximation algorithms for maximum cut and satisfiability problems using semidefinite programming. J ACM 42:1115–1145
Kale S, Seshadhri C (2010) Combinatorial approximation algorithms for MaxCut using random walks (preprint). arXiv:1008.3938
Lewin M, Livnat D, Zwick U (2002) Improved rounding techniques for the MAX \(2\)-SAT and MAX DI-CUT problems. In: Proceedings of the 9th international conference on integer programming and combinatorial optimization, pp 67–82
Nikiforov V (2016) Max \(k\)-cut and the smallest eigenvalue. Linear Algebra Appl 504:462–467
Soto A (2015) Improved analysis of Max-Cut algorithm based on spectral partitioning. SIAM J Discrete Math 29:259–268
Trevisan L (2012) Max cut and the smallest eigenvalue. SIAM J Comput 41:1769–1786
Acknowledgements
The first author is supported by Beijing Excellent Talents Funding (No. 201400 0020124G046), and General Science and Technology Project of Beijing Municipal Education Commission (No. KM201810005006). The second author’s research is supported by the Natural Sciences and Engineering Research Council of Canada (NSERC) Grant 06446, and NSFC (Nos. 11771386 and 11728104). The third author’s research is supported by NSFC (No. 11501412). The fourth author’s research is supported by NSFC (Nos. 11531014 and 11871081). The fifth author is supported by Higher Educational Science and Technology Program of Shandong Province (No. J15LN22).
Author information
Authors and Affiliations
Corresponding author
Additional information
Publisher's Note
Springer Nature remains neutral with regard to jurisdictional claims in published maps and institutional affiliations.
A preliminary version of this paper appeared in Proceedings of the 11th International Conference on Combinatorial Optimization and Applications, pp 298–312, 2017.
Appendix
Appendix
We give the proof of Lemma 2. The probability of a cut arc is given by
Similarly, the probability of a crossing arc can be obtained by
In the following, we prove equation (10). Note that the vector x is derived by Algorithm 1. We consider three cases.
-
Case 1.
If \(x_{i}\) and \(x_{j}\, (i,j\in \{1,2,\ldots ,n\})\) are both equal to zero, (10) holds obviously.
-
Case 2.
If exactly one of \(x_{i}\) and \(x_{j}\) is zero, then for symmetry, assume that \(x_{i}\) is zero.
-
Case 2.1.
\(x_{j}\ne 0\) and \(x_jx_0\ge 0\). We obtain \(C(i,j)=0\) and \(X(i,j)=x_{0}^{2}x_{j}^2\). Then, we have
$$\begin{aligned} \begin{aligned} C(i,j)+\beta X(i,j)&\ge \beta (1-\beta ) x_{0}^{2}x_{j}^2\\&=\beta (1-\beta ) x_{0}^{2}\left( x_{j}^2-2x_{0}x_{j}\right) +2\beta (1-\beta )x^3_{0}x_{j}\\&\ge \beta (1-\beta ) x_{0}^{2}\left( x_{j}^2-2x_{0}x_{j}\right) -2\beta (1-\beta )x^2_{0}x^2_{j}.\\ \end{aligned} \end{aligned}$$ -
Case 2.2.
\(x_{j}\ne 0\) and \(x_jx_0\le 0\). We easily obtain \(C(i,j)=0\) and \(X(i,j)=x_{0}^2x_{j}^2\). Since \(-x_{0}x_{j}\le x_{j}^{2}\), we get
$$\begin{aligned} \begin{aligned} C(i,j)+\beta X(i,j)&\ge \beta (1-\beta )x_{0}^{2}x_{j}^2\\&=\beta (1-\beta )x_{0}^{2}(x_{j}^{2}-2x_{0}^{2}x_{j})+2\beta (1-\beta )x_{0}^{3}x_{j}\\&\ge \beta (1-\beta )x_{0}^{2}(x_{j}^{2}-2x_{0}^{2}x_{j})-2\beta (1-\beta )x_{0}^{2}x_{j}^{2}. \end{aligned} \end{aligned}$$
Equation (10) holds in these cases.
-
Case 2.1.
-
Case 3.
\(x_{i}x_{j}\ne 0\). According to the signs and the sizes of \(x_{i}\) and \(x_{j}\), we consider eight cases in the following.
-
Case 3.1.
\(x_{0}x_{i}> 0\), \(x_{0}x_{j}> 0\), and \(|x_{0}x_{j}| \le |x_{0}x_{i}|\) (\( x_{0}x_{j}\le x_{0}x_{i}\)). Then we have
$$\begin{aligned} \begin{aligned} C(i,j)=&0,\\ X(i,j)=&\mathbb {P}\left\{ |x_{0}x_{j}|\le \sqrt{t}<x_{0}x_{i}\right\} =x_{0}^2x_{i}^2-x_{0}^2x_{j}^2, \end{aligned} \end{aligned}$$and
$$\begin{aligned} \begin{aligned} C(i,j)+\beta X(i,j)=\,&\beta \left( x_{0}^2x_{i}^2-x_{0}^2x_{j}^2\right) \\ =\,&\beta \left( x_{0}x_{i}+x_{0}x_{j}\right) \left( x_{0}x_{i}-x_{0}x_{j}\right) \\ \ge \,&\beta (1-\beta )\left( x_{0}x_{i}-x_{0}x_{j}\right) ^{2}\\ =\,&\beta (1-\beta )\left( x_{0}^2x_{i}^2+x_{0}^2x_{j}^2-2x_{0}^2x_{i}x_{j}\right) \\ =\,&\beta (1-\beta )x_{0}^2\left( x_{i}^2+x_{j}^2+2x_{0}x_{i}-2x_{0}x_{j} -2x_{i}x_{j}\right) \\ \,&-\beta (1-\beta )x_{0}^2\left( 2x_{0}x_{i}-2x_{0}x_{j}\right) . \end{aligned} \end{aligned}$$Since \(x_{0}^2\le x_{0}x_{i}+x_{0}x_{j}\), we get
$$\begin{aligned} \begin{aligned} 2x_{0}^2\left( x_{0}x_{i}-x_{0}x_{j}\right) \le \,&2\left( x_{0}x_{i} +x_{0}x_{j}\right) \left( x_{0}x_{i}-x_{0}x_{j}\right) \\ =\,&2\left( x_{0}^2x_{i}^2-x_{0}^2x_{j}^2\right) =2X(i,j). \end{aligned} \end{aligned}$$Therefore,
$$\begin{aligned} \begin{aligned} -\beta (1-\beta )x_{0}^2\left( 2x_{0}x_{i}-2x_{0}x_{j}\right) \ge&-\beta (1-\beta )2X(i,j)\\ =&-\beta (1-\beta )2X(i,j)-\beta (1-\beta )4C(i,j). \end{aligned} \end{aligned}$$Finally,
$$\begin{aligned} \begin{aligned} C(i,j)+\beta X(i,j)&\ge \beta (1-\beta )x_{0}^2\left( x_{i}^2+x_{j}^2+2x_{0}x_{i}-2x_{0}x_{j}-2x_{i}x_{j}\right) \\&\quad -\beta (1-\beta )\left[ 2X(i,j)+4C(i,j)\right] . \end{aligned} \end{aligned}$$ -
Case 3.2.
\(x_{i}\), \(x_{j}\) and \(x_{0}\) all have the same sign, and \(|x_{0}x_{i}|\le |x_{0}x_{j}|\) (\(x_{0}x_{i}\le x_{0}x_{j}\)). Then, we have
$$\begin{aligned} \begin{aligned} C(i,j)&=0,\\ X(i,j)&=\mathbb {P}\left\{ |x_{0}x_{i}|\le \sqrt{t}<x_{0}x_{j}\right\} =x_{0}^2x_{j}^2-x_{0}^2x_{i}^2, \end{aligned} \end{aligned}$$and
$$\begin{aligned} \begin{aligned} C(i,j)+\beta X(i,j)=\,&\beta \left( x_{0}^2x_{j}^2-x_{0}^2x_{i}^2\right) \\ =\,&\beta \left( x_{0}x_{j}+x_{0}x_{i}\right) \left( x_{0}x_{j}-x_{0}x_{i}\right) \\ \ge \,&\beta (1-\beta )\left( x_{0}x_{j}-x_{0}x_{i}\right) ^{2}\\ =\,&\beta (1-\beta )\left( x_{0}^2x_{i}^2+x_{0}^2x_{j}^2-2x_{0}^2x_{i}x_{j}\right) \\ =\,&\beta (1-\beta )x_{0}^2\left( x_{i}^2+x_{j}^2+2x_{0}x_{i}-2x_{0}x_{j} -2x_{i}x_{j}\right) \\ \,&-\beta (1-\beta )x_{0}^2\left( 2x_{0}x_{i}-2x_{0}x_{j}\right) . \end{aligned} \end{aligned}$$Since \(x_{0}x_{i}-x_{0}x_{j}\le 0\), we have \(-\beta (1-\beta )x_{0}^2 \left( 2x_{0}x_{i}-2x_{0}x_{j}\right) \ge 0\). Moreover, \(-\left( x_{0}x_{j}+x_{0}x_{i}\right) \le 0\). Therefore
$$\begin{aligned} \begin{aligned}&-\beta (1-\beta )x_{0}^2\left( 2x_{0}x_{i}-2x_{0}x_{j}\right) \ge 0\\&\quad \ge -\beta (1-\beta )x_{0}^2\left( 2x_{0}x_{i}-2x_{0}x_{j}\right) \left[ -\left( x_{0} x_{i}+x_{0}x_{j}\right) \right] \\&\quad \ge -\beta (1-\beta )2\left( x_{0}^2x_{j}^2-x_{0}^2x_{i}^2\right) \\&\quad =-\beta (1-\beta )2X(i,j)\\&\quad =-\beta (1-\beta )\left[ 2X(i,j)+4C(i,j)\right] . \end{aligned} \end{aligned}$$Finally,
$$\begin{aligned} \begin{aligned} C(i,j)+\beta X(i,j)\ge&\,\beta (1-\beta )x_{0}^2\left( x_{i}^2+x_{j}^2+2x_{0}x_{i}-2x_{0}x_{j}-2x_{i}x_{j}\right) \\&-\beta (1-\beta )\left[ 2X(i,j)+4C(i,j)\right] . \end{aligned} \end{aligned}$$ -
Case 3.3
\(x_{0}x_{i}< 0\), \(x_{0}x_{j}< 0\) and \(|x_{0}x_{j}|\le |x_{0}x_{i}|\) (\(x_{0}x_{i}\le x_{0}x_{j}\)). Then, we have
$$\begin{aligned} \begin{aligned} C(i,j)&= 0,\\ X(i,j)&= \mathbb {P}\left\{ |x_{0}x_{j}|\le \sqrt{t}<-x_{0}x_{i}\right\} =x_{0}^2x_{i}^2-x_{0}^2x_{j}^2, \end{aligned} \end{aligned}$$and
$$\begin{aligned} \begin{aligned} C(i,j)+\beta X(i,j)&= \beta \left( x_{0}^2x_{i}^2-x_{0}^2x_{j}^2\right) \\&\ge \beta (1-\beta )\left| x_{0}x_{i}+x_{0}x_{j}\right| \left| x_{0}x_{i} -x_{0}x_{j}\right| \\&\ge \beta (1-\beta )\left( x_{0}x_{i}-x_{0}x_{j}\right) ^{2}\\&= \beta (1-\beta )\left( x_{0}^2x_{i}^2+x_{0}^2x_{j}^2-2x_{0}^2x_{i}x_{j}\right) \\&= \beta (1-\beta )x_{0}^2\left( x_{i}^2+x_{j}^2+2x_{0}x_{i}-2x_{0}x_{j} -2x_{i}x_{j}\right) \\&\quad -\,\beta (1-\beta )x_{0}^2\left( 2x_{0}x_{i}-2x_{0}x_{j}\right) . \end{aligned} \end{aligned}$$Because of \(\left| x_{0}x_{i}-x_{0}x_{j}\right| \le \left| x_{0}x_{i} +x_{0}x_{j}\right| \), the third inequality follows from the second one. Since \(\left( x_{0}x_{i}-x_{0}x_{j}\right) \le 0\), we have
$$\begin{aligned} -\beta (1-\beta )x_{0}^2\left( 2x_{0}x_{i}-2x_{0}x_{j}\right) \ge 0. \end{aligned}$$Moreover \(\left( x_{0}x_{i}+x_{0}x_{j}\right) \le 0\), we have
$$\begin{aligned} \begin{aligned}&-\beta (1-\beta )x_{0}^2\left( 2x_{0}x_{i}-2x_{0}x_{j}\right) \ge 0\\&\quad \ge -\beta (1-\beta )x_{0}^2\left( 2x_{0}x_{i}-2x_{0}x_{j}\right) \left( x_{0} x_{i}+x_{0}x_{j}\right) \\&\quad \ge -\beta (1-\beta )2\left( x_{0}^2x_{i}^2-x_{0}^2x_{j}^2\right) \\&\quad =-\beta (1-\beta )\left[ 2X(i,j)+4C(i,j)\right] . \end{aligned} \end{aligned}$$Therefore,
$$\begin{aligned} \begin{aligned} C(i,j)+\beta X(i,j)&\ge \beta (1-\beta )x_{0}^2\left( x_{i}^2+x_{j}^2 +2x_{0}x_{i}-2x_{0}x_{j}-2x_{i}x_{j}\right) \\&\quad -\beta (1-\beta )\left[ 2X(i,j)+4C(i,j)\right] . \end{aligned} \end{aligned}$$ -
Case 3.4.
\(x_{0}x_{i}<0\), \(x_{0}x_{j}<0\), and \(|x_{0}x_{i}|\le |x_{0}x_{j}|\) (\(x_{0}x_{j}\le x_{0}x_{i}\)). Then, we have
$$\begin{aligned} \begin{aligned} C(i,j)&=0,\\ X(i,j)&=\mathbb {P}\left\{ |x_{0}x_{i}|\le \sqrt{t}<-x_{0}x_{j}\right\} =x_{0}^2x_{j}^2-x_{0}^2x_{i}^2, \end{aligned} \end{aligned}$$and
$$\begin{aligned} \begin{aligned} C(i,j)+\beta X(i,j)&=\beta \left( x_{0}^2x_{j}^2-x_{0}^2x_{i}^2\right) \\&\ge \beta (1-\beta )\left| x_{0}x_{i}+x_{0}x_{j}\right| \left| x_{0}x_{i} -x_{0}x_{j}\right| \\&\ge \beta (1-\beta )\left( x_{0}x_{j}-x_{0}x_{i}\right) ^{2}\\&=\beta (1-\beta )\left( x_{0}^2x_{i}^2+x_{0}^2x_{j}^2-2x_{0}^2x_{i}x_{j}\right) \\&=\beta (1-\beta )x_{0}^2\left( x_{i}^2+x_{j}^2+2x_{0}x_{i}-2x_{0}x_{j} -2x_{i}x_{j}\right) \\&\quad -\beta (1-\beta )x_{0}^2\left( 2x_{0}x_{i}-2x_{0}x_{j}\right) . \end{aligned} \end{aligned}$$Because of \(\left| x_{0}x_{i}-x_{0}x_{j}\right| \le \left| x_{0}x_{i} +x_{0}x_{j}\right| \), the third inequality follows from the second one. Meanwhile, from \(x_{0}^2\le -\left( x_{0}x_{i}+x_{0}x_{j}\right) \) and
$$\begin{aligned} \begin{aligned} x_{0}^2\left( 2x_{0}x_{i}-2x_{0}x_{j}\right)&\le -\left( x_{0}x_{i} +x_{0}x_{j}\right) \left( 2x_{0}x_{i}-2x_{0}x_{j}\right) \\&=2\left( x_{0}^2x_{j}^2-x_{0}^2x_{i}^2\right) \\&=2X(i,j), \end{aligned} \end{aligned}$$we have
$$\begin{aligned} \begin{aligned} C(i,j)+\beta X(i,j)&\ge \beta (1-\beta )x_{0}^2\left( x_{i}^2+x_{j}^2+2x_{0}x_{i}-2x_{0}x_{j}-2x_{i}x_{j}\right) \\&\quad -\beta (1-\beta )\left[ 2X(i,j)+4C(i,j)\right] . \end{aligned} \end{aligned}$$ -
Case 3.5.
\(x_{0}x_{i}> 0\), \(x_{0}x_{j}<0\), and \(|x_{0}x_{j}|\le |x_{0}x_{i}|\) (\(-x_{0}x_{j}\le x_{0}x_{i}\)). Then, we have
$$\begin{aligned} \begin{aligned} C(i,j)=&x_{0}^2x_{j}^2,\\ X(i,j)=&\mathbb {P}\left\{ |x_{0}x_{j}|\le \sqrt{t}<x_{0}x_{i}\right\} =x_{0}^2x_{i}^2-x_{0}^2x_{j}^2. \end{aligned} \end{aligned}$$The inequality (Beckenbach and Bellman 1961)
$$\begin{aligned} (1-\beta )a^2+\beta b^2\ge \beta (1-\beta )(a+b)^{2} \end{aligned}$$holds for \(a,b\ge 0\), and \(0\le \beta \le 1\). Since \(x_{0}x_{i}>0\), \(-x_{0}x_{j}>0\), we obtain that
$$\begin{aligned} C(i,j)+\beta X(i,j)&=x_{0}^2x_{j}^2+\beta \left( x_{0}^2x_{i}^2-x_{0}^2x_{j}^2\right) \\&=\beta x_{0}^2x_{i}^2+(1-\beta )x_{0}^2x_{j}^2\\&\ge \beta (1-\beta )\left( x_{0}x_{i}-x_{0}x_{j}\right) ^{2}\\&=\beta (1-\beta )\left( x_{0}^2x_{i}^2+x_{0}^2x_{j}^2-2x_{0}^2x_{i}x_{j}\right) \\&=\beta (1-\beta )x_{0}^2\left( x_{i}^2+x_{j}^2+2x_{0}x_{i}-2x_{0}x_{j}-2x_{i}x_{j}\right) \\&\quad -\beta (1-\beta )x_{0}^2\left( 2x_{0}x_{i}-2x_{0}x_{j}\right) . \end{aligned}$$Since \(x_{0}x_{i}>0\) and \(x_{0}x_{j}<0\), we have \(x_{0}x_{i}-x_{0}x_{j}>0\), \(x_{0}x_{i}+x_{0}x_{j}>0\), and
$$\begin{aligned} \begin{aligned} x_{0}^2\left( 2x_{0}x_{i}-2x_{0}x_{j}\right)&\le -x_{0}x_{j}\left( 2x_{0}x_{i}-2x_{0}x_{j}\right) \\&=2\left( x_{0}^2x_{j}^2+x_{0}x_{i}(-x_{0}x_{j})\right) \\&\le 2\left( x_{0}^2x_{j}^2+x_{0}^2x_{i}^2)\right) \\&=2\left( x_{0}^2x_{j}^2+x_{0}^2x_{i}^2-x_{0}^2x_{j}^2+x_{0}^2x_{j}^2)\right) \\&=2X(i,j)+4C(i,j). \end{aligned} \end{aligned}$$Therefore,
$$\begin{aligned} \begin{aligned} -\beta (1-\beta )x_{0}^2\left( 2x_{0}x_{i}-2x_{0}x_{j}\right) \ge -\beta (1-\beta )\left[ 2X(i,j)+4C(i,j)\right] . \end{aligned} \end{aligned}$$Finally,
$$\begin{aligned} \begin{aligned} C(i,j)+\beta X(i,j)&\ge \beta (1-\beta )x_{0}^2\left( x_{i}^2+x_{j}^2+2x_{0}x_{i}-2x_{0}x_{j}-2x_{i} x_{j}\right) \\&\quad -\beta (1-\beta )\left[ 2X(i,j)+4C(i,j)\right] . \end{aligned} \end{aligned}$$ -
Case 3.6.
\(x_{0}x_{i}> 0\), \(x_{0}x_{j}< 0\), and \(|x_{0}x_{i}|\le |x_{0}x_{j}|\) (\( x_{0}x_{i}\le -x_{0}x_{j}\)). Then, we have
$$\begin{aligned} \begin{aligned} C(i,j)=&x_{0}^2x_{i}^2,\\ X(i,j)=&\mathbb {P}\left\{ |x_{0}x_{i}|\le \sqrt{t}<-x_{0}x_{j}\right\} =x_{0}^2x_{j}^2-x_{0}^2x_{i}^2, \end{aligned} \end{aligned}$$and
$$\begin{aligned} \begin{aligned} C(i,j)+\beta X(i,j)&= x_{0}^2x_{i}^2+\beta \left( x_{0}^2x_{j}^2-x_{0}^2x_{i}^2\right) \\&=\beta x_{0}^2x_{j}^2+(1-\beta )x_{0}^2x_{i}^2\\&\ge \beta (1-\beta )\left( x_{0}x_{j}-x_{0}x_{i}\right) ^{2}\\&=\beta (1-\beta )\left( x_{0}^2x_{i}^2+x_{0}^2x_{j}^2-2x_{0}^2x_{i}x_{j}\right) \\&=\beta (1-\beta )x_{0}^2\left( x_{i}^2+x_{j}^2+2x_{0}x_{i}-2x_{0}x_{j} -2x_{i}x_{j}\right) \\&\quad -\beta (1-\beta )x_{0}^2\left( 2x_{0}x_{i}-2x_{0}x_{j}\right) . \end{aligned} \end{aligned}$$It is easy to get \(x_{0}x_{i}-x_{0}x_{j}>0\), \(x_{0}x_{i}+x_{0}x_{j}>0\), and
$$\begin{aligned} \begin{aligned} x_{0}^2\left( 2x_{0}x_{i}-2x_{0}x_{j}\right)&\le x_{0}x_{i}\left( 2x_{0} x_{i}-2x_{0}x_{j}\right) \\&= 2\left( x_{0}^2x_{i}^2+x_{0}x_{i}(-x_{0}x_{j})\right) \\&\le 2\left( x_{0}^2x_{i}^2+x_{0}^2x_{j}^2\right) \\&= 2\left( x_{0}^2x_{i}^2+x_{0}^2x_{j}^2-x_{0}^2x_{i}^2+x_{0}^2x_{i}^2\right) \\&= 2X(i,j)+4C(i,j). \end{aligned} \end{aligned}$$Therefore,
$$\begin{aligned} \begin{aligned} -\beta (1-\beta )x_{0}^2\left( 2x_{0}x_{i}-2x_{0}x_{j}\right) \ge -\beta (1-\beta )\left[ 2X(i,j)+4C(i,j)\right] . \end{aligned} \end{aligned}$$Finally,
$$\begin{aligned} \begin{aligned} C(i,j)+\beta X(i,j)&\ge \beta (1-\beta )x_{0}^2\left( x_{i}^2+x_{j}^2 +2x_{0}x_{i}-2x_{0}x_{j}-2x_{i}x_{j}\right) \\&\quad -\beta (1-\beta )\left[ 2X(i,j)+4C(i,j)\right] . \end{aligned} \end{aligned}$$ -
Case 3.7.
\(x_{0}x_{i}< 0\), \(x_{0}x_{j}> 0\), and \(|x_{0}x_{j}|\le |x_{0}x_{i}|\) (\(x_{0}x_{j}\le -x_{0}x_{i}\)). Then, we have
$$\begin{aligned} \begin{aligned} C(i,j)&=x_{0}^2x_{j}^2,\\ X(i,j)&=\mathbb {P}\left\{ |x_{0}x_{j}|\le \sqrt{t}<-x_{0}x_{i}\right\} =x_{0}^2x_{i}^2-x_{0}^2x_{j}^2, \end{aligned} \end{aligned}$$and
$$\begin{aligned} C(i,j)+\beta X(i,j)&=x_{0}^2x_{j}^2+\beta \left( x_{0}^2x_{i}^2 -x_{0}^2x_{j}^2\right) \\&=\beta x_{0}^2x_{i}^2+(1-\beta )x_{0}^2x_{j}^2\\&\ge \beta (1-\beta )\left( x_{0}x_{i}-x_{0}x_{j}\right) ^{2}\\&=\beta (1-\beta )\left( x_{0}^2x_{i}^2+x_{0}^2x_{j}^2-2x_{0}^2x_{i}x_{j}\right) \\&=\beta (1-\beta )x_{0}^2\left( x_{i}^2+x_{j}^2+2x_{0}x_{i}-2x_{0} x_{j}-2x_{i}x_{j}\right) \\&\quad -\beta (1-\beta )x_{0}^2\left( 2x_{0}x_{i}-2x_{0}x_{j}\right) . \end{aligned}$$Since \(x_{0}x_{i}+x_{0}x_{j}\le 0\), we have
$$\begin{aligned}&-\beta (1-\beta ) x_{0}^2\left( 2x_{0}x_{i}-2x_{0}x_{j}\right) \ge 0\\&\quad \ge -\beta (1-\beta ) x_{0}^2\left( 2x_{0}x_{i}-2x_{0}x_{j}\right) \left( x_{0} x_{i}+x_{0}x_{j}\right) \\&\quad \ge -\beta (1-\beta )2\left( x_{0}^2x_{i}^2-x_{0}^2x_{j}^2\right) \\&\quad =-\beta (1-\beta )2X(i,j)\\&\quad \ge -\beta (1-\beta )\left[ 2X(i,j)+4C(i,j)\right] . \end{aligned}$$Therefore,
$$\begin{aligned} \begin{aligned} C(i,j)+\beta X(i,j)&\ge \beta (1-\beta )x_{0}^2\left( x_{i}^2+x_{j}^2+2 x_{0}x_{i}-2x_{0}x_{j}-2x_{i}x_{j}\right) \\&\quad -\beta (1-\beta )\left[ 2X(i,j)+4C(i,j)\right] . \end{aligned} \end{aligned}$$ -
Case 3.8.
\(x_{i}x_{0}< 0\), \(x_{j}x_{0}> 0\), and \(|x_{0}x_{i}| \le |x_{0}x_{j}|\) (\( -x_{0}x_{i}\le x_{0}x_{j}\)). Then, we have
$$\begin{aligned} \begin{aligned} C(i,j)&=x_{0}^2x_{i}^2,\\ X(i,j)&=\mathbb {P}\left\{ |x_{0}x_{i}|\le \sqrt{t}<-x_{0}x_{j}\right\} =x_{0}^2x_{j}^2-x_{0}^2x_{i}^2, \end{aligned} \end{aligned}$$and
$$\begin{aligned} \begin{aligned} C(i,j)+\beta X(i,j)&=x_{0}^2x_{i}^2+\beta \left( x_{0}^2x_{j}^2-x_{0}^2 x_{i}^2\right) \\&=\beta x_{0}^2x_{j}^2+(1-\beta )x_{0}^2x_{i}^2\\&\ge \beta (1-\beta )\left( x_{0}x_{j}-x_{0}x_{i}\right) ^{2}\\&=\beta (1-\beta )\left( x_{0}^2x_{i}^2+x_{0}^2x_{j}^2-2x_{0}^2x_{i}x_{j}\right) \\&=\beta (1-\beta )x_{0}^2\left( x_{i}^2+x_{j}^2+2x_{0}x_{i}-2x_{0}x_{j}-2 x_{i}x_{j}\right) \\&\quad -\beta (1-\beta )x_{0}^2\left( 2x_{0}x_{i}-2x_{0}x_{j}\right) . \end{aligned} \end{aligned}$$Since \(x_{0}x_{i}+x_{0}x_{j}\ge 0\) and \(-\left( x_{0}x_{i}+x_{0}x_{j}\right) \le 0\), we have
$$\begin{aligned}&-\beta (1-\beta ) x_{0}^2\left( 2x_{0}x_{i}-2x_{0}x_{j}\right) \ge 0\\&\quad \ge -\beta (1-\beta ) x_{0}^2\left( 2x_{0}x_{i}-2x_{0}x_{j}\right) \left[ -\left( x_{0} x_{i}+x_{0}x_{j}\right) \right] \\&\quad \ge -\beta (1-\beta )2\left( x_{0}^2x_{j}^2-x_{0}^2x_{i}^2\right) \\&\quad =-\beta (1-\beta )2X(i,j)\\&\quad \ge -\beta (1-\beta )\left[ 2X(i,j)+4C(i,j)\right] . \end{aligned}$$Therefore,
$$\begin{aligned} \begin{aligned} C(i,j)+\beta X(i,j)\ge \,&\beta (1-\beta )x_{0}^2\left( x_{i}^2+x_{j}^2+2x_{0} x_{i}-2x_{0}x_{j}-2x_{i}x_{j}\right) \\&-\,\beta (1-\beta )\left[ 2X(i,j)+4C(i,j)\right] . \end{aligned} \end{aligned}$$
-
Case 3.1.
Rights and permissions
About this article
Cite this article
Zhang, Z., Du, D., Wu, C. et al. A spectral partitioning algorithm for maximum directed cut problem. J Comb Optim 42, 373–395 (2021). https://doi.org/10.1007/s10878-018-0369-4
Published:
Issue Date:
DOI: https://doi.org/10.1007/s10878-018-0369-4
Keywords
Profiles
- Dachuan Xu View author profile